Hubungan antara Ukuran Tumor, Grade, Invasi Uretra, Intravasa, Perineural dan Overekspresi COX-2 pada Metastasis Karsinoma Sel Skuamosa Penis ke Kelenjar Getah Bening Inguinal - Desak Putu Oki Lestari; Ketut Mulyadi Mulyadi (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2018)
Background Penile cancer was a health problem in Bali. Clinicopathology and biological marker COX-2 were important predictive factor used for inguinal lymph node metastasis. The aim of this study was to find out relationship between clinicopathological prognostic factors (tumor size, grade, urethral invasion, intra vasa invasion, perineural invasion) and COX-2 exprerssion in metastases of SCC penile to the inguinal lymph nodes. Methods This observational crossectional study included 47 samples of SCC penis preparation from penectomy with inguinal lymphadenectomy since January 1st 2008-Desember 31st 2013 at Department of Anatomical Pathology Faculty of Medicine University of Udayana/Sanglah Hospital Denpasar. Sample of this study was divided into 2 groups: 16 cases SCC positive metastasis and 31 cases negative metastasis. Rediagnosis clinico-pathological prognostic factor was done, immunohistochemistry COX-2 staining was performed. The data were analized using chi-square (Î±=0.05). Results This study show significant positive correlation between tumor size â‰¥5 cm (p=0.002), grade (p=0.002), urethra invasion (p=0.014), intra vasa invasion (p=0.00), perineural invasion (p=0.00) with metastasis. COX-2 expression (+2) and (+3) have higher risk on occurrence of metastasis than (0) and (+1) (p=0.00). Conclusion Clinico-pathologic factors and COX-2 expression could be used to predict metastases of SCC penile to the inguinal lymph nodes. Key words: clinicopathologic prognosis factor, COX-2, inguinal lymph nodes metastasis, squamous cells carcinoma penis.